Prospective evaluation of the aetiology of acute otitis media with spontaneous tympanic membrane perforation. (July 2017) - ,; Gallia, P.; Mazzucchi, E.; Onorato, J.; Russo, A.; Vaccarino, A.M.; Marchisio, P.; Esposito, S.; Picca, M.; Baggi, E.; Terranova, L.; Orenti, A.; et al.
Abstract: Objectives: To evaluate the aetiological role of the main bacterial pathogens associated with acute otitis media (AOM) in children with AOM and spontaneous tympanic membrane perforation (STMP). Methods: Between 1 May 2015 and 30 April 2016, 177 children, aged 6 months to 7 years, with AOM complicated by STMP within 12 h were prospectively enrolled. Middle ear fluid (MEF) was tested by real-time PCR for Streptococcus pneumoniae, non-typeable Haemophilus influenzae, Streptococcus pyogenes, Moraxella catarrhalis and Staphylococcus aureus . Results: Among the 177 children with AOM and STMP, 92/100 (92.0%) of those with recurrent AOM and 13/77 (16.9%) without recurrent AOM had recurrent STMP (p <0.001). A single pathogen was identified in 70 (39.5%) MEF samples, whereas two, three and four bacteria were detected in 54 (30.5%), 20 (11.3%), and 7 (4.0%) cases, respectively. Non-typeable H. influenzae was the most common and was identified in 90 children (50.8%), followed by M. catarrhalis (62 cases, 35.0%) and S. pneumoniae (48 cases, 27.1%). Non-typeable H. influenzae was the most frequent pathogen in children with co-infections. Children with co-infections, including non-typeable H. influenzae, had significantly more frequent recurrent AOM (adjusted OR 6.609, 95% CI 1.243–39.096, p 0.029). Conclusions: Recurrent AOM episodes appear to be associated with an increased risk of AOM with STMP. In AOM with STMP, non-typeable H. influenzae is detected at a high frequency, especially in children with recurrent STMP and often in association with other pathogens.